Satisfaction and intention of food-based Mardi entrepreneurs towards Mardi’s consultancy and advisory services - Kasron, Norzalila (2019)
The Malaysian government has emphasised on the importance of SMEs in enhancing the dynamism and competitiveness of the manufacturing sector. Considerable attention has been given to the provision of industrial infrastructure and amenities to facilitate the expansion of SMEs activities. Malaysian Agricultural Research and Development Institute (MARDI) is one of the agencies under the Ministry of Agriculture that is involved in giving services to entrepreneurs development. The services rendered to MARDI’s entrepreneurs was in the form of soft technology such as advisory and consultation services. To date, entrepreneurs have successfully brought numerous products to the export market through MARDI’s services rendered in the form of consultation and advisory on soft technology. A study was undertaken to investigate service quality satisfaction among SME’s entrepreneurs in utilizing the consultancy and advisory services rendered and intention to continuously use services form MARDI. The study also want to identify service quality dimensions of entrepreneur’s satisfaction as well as to examine the disparity between expectation and actual service quality as perceived and experienced. The sampling frame of this study was MARDI’s entrepreneurs. The respondents were selected by simple random sampling technique to ensure that every component of the population received equal chance of being part of the selected sample. The sampling technique, the most straight forward method of probability sampling, allowed sampling error to be calculated and reduced selection bias. Sample size was determined based on 95% confidence level and 5% confidence interval. Questionnaire was developed as an instrument of the study consisting of questions on service quality model. A multi-dimensional research instrument, Service Quality Model (SERVQUAL Model) was used to capture entrepreneurs’ satisfaction, intention, expectations and perceptions along five dimensions representing service quality. Since MARDI’s core business is in research and development (R&D), technology was added as an additional dimension. GAP analysis was used to measure the differences between entrepreneurs’ expectation and perception performances either potential or desired. Structural Equation Modeling (SEM) was used to analyze data. From the model, six dimensions directly contributed to satisfaction. Four dimensions were statistically significant: reliability, responsiveness, assurance and technology, affecting satisfaction of entrepreneurs to continuously use services from MARDI. Tangibility and empathy dimensions were not significant. The study revealed that all dimensions in perceptions exceeded expectation except for responsiveness and technology. Confirmatory Factor Analysis (CFA) revealed that the variables used fit the model at 0.001 significance. Reliability test found that the variables used fit the SEM where the entire factor loading was more than 0.6. The model showed an agreeable χ2/df with index of 1.721. Fit indices of CFI = 0.942 and TLI = 0.935 achieved higher than the threshold indicating that the structural model falls within the agreeable range. Considering the entire fit indices, it is concluded that the data fit the model satisfactorily. Tangibility was significantly not related to satisfaction (β: 0.065, p = 0.318). However, reliability and responsiveness showed that magnitude of the relationship with satisfaction was significant with value of (β: 0.496, p < 0.001) and (β: 0.523, p < 0.001) respectively. The relationships between empathy with satisfaction were not significant (β: 0.055, p = 0.425) while the relationships between assurance and technology to satisfaction were found to be significant (β: 0.213, p < 0.001) and (β: 0.654, p < 0.001) respectively. There was similar occurrence in the relationship between satisfaction and intention of the entrepreneurs where the magnitude of the relationships between satisfaction to intention was strongly supported by a significant relationship (β: 0.600, p < 0.001). The study proposes improvement on MARDI’s services to help MARDI entrepreneur’s to grow their business thus improve the productivity of food products in Malaysia.